Іnvestigation of the causes of the crimination of turbine castings after operation of 100 thousands hours - Tkachenko, D.; Ткаченко, Д. М. (Харківський національний автомобільно-дорожній універститет, 2024)
One of the most important tasks of power engineering is to increase the reliability and performance of turbine parts. In our work, the research material was casting of a steam distribution housing made of steel 15Х2М2ФБС turbine Pridneprovskaya state district power station after operating 100 thousand hours. One of the main factors preventing the formation of a stone-like fracture is the purity of steel and, above all, the absence of sulfides and nitrides.
Дослідження причин окрихчування виливків турбін після експлуатації 100 тис. годин
Keywords: turbine; stone-like fracture; steel purity; sulfides; nitrides; турбіна; кам'яноподібний злам; чистота сталі; сульфіди; нітриди; 621.785